EFFORTS TO PREVENT INDICATIONS OF CRIMINAL ACTS IN NOTARIAL DEEDS THROUGH THE APPLICATION OF ARTICLE 39 PARAGRAPH (2) OF THE UUJN: CRIMINOLOGY STUDIES - Syukur, M. Jafar; Sakmaf, Marius Suprianto; Karauwan, Donny (Al-Risalah, 2023)
Indications of criminal acts by notaries as state public officials are rife in Indonesia. The existence of notary authority in terms of making authentic deeds continues to reap the spotlight ranging from allegations of forgery of letters, embezzlement, money laundering and false information. This study aims to determine efforts to prevent indications of criminal acts in notary deeds through the application of article 39 paragraph 2 of the UUJB. The type of research used is a literature study with a normative juridical approach. The results showed that Article 39 paragraph 2 of the UUJBN was placed as an important instrument in preventing indications of criminal acts in the authority to make notary deeds, the existence of Article 39 paragraph 2 of the UUJB places notaries on objects that are able to act legally by providing formal certainty for authentic deeds made without causing indications of criminal acts. Procedurally, the application of Article 39 paragraph 2 of the UUJB in the prevention of criminal acts is carried out through the precautionary and systematic principle by requiring notaries to know the facing parties and also pay attention to other aspects including certainty of the day, date, month, year and time of face, signatures, copies of deeds, and minutes of deeds issued. In addition, the roles and responsibilities of notaries in making deeds based on Article 39 paragraph 2 of the UUJB include civil responsibility, code of ethics responsibility, administrative responsibility and criminal responsibility.